Frequencies, Timing, and Spatial Patterns of Co-Suppression of Nitrate Reductase and Nitrite Reductase in Transgenic Tobacco Plants. - Palauqui, J. C. (1996)
Frequencies, timing, and spatial patterns of co-suppression of the nitrate (Nia) and nitrite (Nii) genes were analyzed in transgenic tobacco (Nicotiana tabacum) plants carrying either Nia or Nii cDNAs under the control of the 35S promoter, or a Nii gene with its own regulatory signals (promoter, introns, and terminator) cloned downstream of two copies of the enhancer of the 35S promoter. We show that (a) the frequencies of transgenic lines affected by co- suppression are similar for the three constructs, ranging from 19 to 25%; (b) Nia and Nii co-suppression are triggered stochastically during a phenocritical period of 2 weeks between germination and flowering; (c) the timing of co-suppression (i.e. the percentage of isogenic plants affected by co-suppression reported as a function of the number of days of culture) differs from one transgenic line to another; (d) the percentage of isogenic plants affected by co-suppression is increased by growing the plants in vitro prior to their transfer to the greenhouse and to the field; and (e) at the end of the culture period, plants are either unaffected, completely co-suppressed, or variegated. Suppressed and nonsuppressed parts of these variegated plants are separated by a vertical plane through the stem in Nia co-suppression, and separated by a horizontal plane in Nii co-suppression.